Microcephaly caused by congenital Zika virus infection and viral detection in maternal urine during pregnancy - Regadas,Vanessa Couras (2018)
Summary Currently Latin America is undergoing a major epidemic of Zika virus, which is transmitted by Aedes mosquitoes. Concern for Zika virus infection has been increasing as it is suspected of causing brain defects in newborns such as microcephaly and, more recently, potential neurological and autoimmune complications including Guillian-Barré syndrome and acute disseminated encephalomyelitis. We describe a case of virus infection in a 25-year-old woman during the first trimester of her pregnancy, confirmed by laboratory tests only for the detection of viral particles in maternal urine, with imaging studies demonstrating the progression of cranial and encephalic changes in the fetus and later in the newborn, such as head circumference reduction, cerebral calcifications and ventriculomegaly.